Parenting Empirical Advances and Intervention Resources - Benedetto, Loredana; Ingrassia, Massimo (IntechOpen, 2018)
Through parenting, adults raise their children and introduce them into the belonging community. Parents are active determinants of their children's well-being, but children themselves are too. The volume focuses on some relevant theoretical issues related to children's and adolescent adjustments, adult maternal and paternal behaviors, and their self-efficacy beliefs and competence interacting with children's characteristics. The volume also presents evidence-based treatments involving parents as key components of the intervention strategies for childhood internalizing/externalizing disorders. Parent behaviors produce changes and consequences in the child's emotive-behavioral adjustment; thus, a modification of the parenting style may be an effective way to help children and to ameliorate the family climate. Practitioners interested in parenting will find in the updated studies here reviewed new suggestions for preventive family interventions.